On combining exact and approximative proceedings for testing problems in unbalanced mixed linear models - Boris Weimann (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
A method for constructing approximative tests for arbitrary linear hypotheses on variance components in unbalanced mixed linear models is derived. The idea of cell mean models is used to derive independent and x2 - distributed mean squares. These modified mean squares are combined to generalized test statistics which lead to generalized fixed level tests.
Keywords: 519